Gendered E-commerce adoption among rural Indonesian entrepreneurs: determinants and income impact - Weni Lidya Sukma; Kadir Ruslan (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2026)
This study investigates gender differences in e-commerce adoption among rural entrepreneurs in Indonesia using nationally representative labor force survey data (Sakernas). It examines the factors that drive adoption among rural men and women and the extent to which adoption improves earnings, as well as how these effects vary by gender and across the income distribution. Probit models and gender-disaggregated income regressions are applied to identify adoption determinants and quantify income impacts. Results show that education and training strongly promote digital uptake, while age, marital status, and household structure constrain participation—particularly for women. E-commerce adoption significantly increases earnings, with male adopters gaining an average 30.8 percent income premium and female adopters 17.5 percent. Quantile regression reveals that low-income men benefit disproportionately, suggesting an equalizing role of digital platforms. Propensity Score Matching confirms a causal effect for male adopters earn approximately IDR 1 million more per week, while women earn IDR 500,000 more. These findings highlight persistent gender gaps in both access and returns, underscoring the need for gender-sensitive digital inclusion policies that address capability deficits and structural barriers limiting women’s full participation in the digital economy.